تخزين طاقة النظم الكهروضوئية عن طريق التحليل الكهربائي للماء - عباس صندوق; غيث ورقوزق (Tishreen University, 2017)
It is known that, the available power from a photovoltaic system is unpredicted and differs with climatic changes, so it has an intermittent nature, in other words it is unable to supply the load continuously and steadily. Because of that, storage methods of its energy must be studied to use it again in a way that could be predicted. Hydrogen production is one of these methods by connecting the PV system to water electrolysers, and this stored hydrogen could be used either in fuel cells or burning it to get thermal energy. This study focuses on PV system and the available energy taken from it, and the electrolysers and its requirements and products. Making a mathematical model would be done and plotting the curves that represent the system by programming it using MATLAB. A simple numeral example that clears the system would be calculated. By this way, the energy efficiency would be between 23 to 67 % according to the way the produced hydrogen is used. من المعروف أنَّ الاستطاعة المتاحة من النظم الكهروضوئية لا يمكن التنبؤ بها وتتغير مع تغير الظروف المناخية لذلك فهي تتميز بطبيعة متقطِّعة أي أنّها غير قادرة على تغذية الحمل بشكل متواصل وبمعدلات ثابتة، لذلك كان لابدَّ من دراسة أساليب تخزين للطاقة الكهربائية المنتجة منها بحيث يتم إعادة استخدام هذه الطاقة بشكل يمكن توقعه، وأحد هذه الطرق هو إنتاج الهيدروجين عن طريق ربط النظم الكهروضوئية مع محلِّلات مياه تقوم بتحليل الماء كهربائياً، و بتخزين هذا الهيدروجين يمكن استخدامه بمعدلات ثابتة إمَّا في خلايا الوقود أو عن طريق حرقه مباشرةً والاستفادة من الطاقة الحرارية المنتجة. هذه الدراسة تُركِّز على النظم الكهروضوئية والطاقة المتاحة منها وعلى المحلِّلات وآلية عملها ومتطلباتها ونواتجها، ووضع النموذج الرياضي الذي يوصِّف أداءها ورسم المنحنيات التي تعبِّر عنها عن طريق برمجتها باستخدام برنامج الماتلاب MATLAB، ووضع مثال عددي بسيط يوضِّح القيم الموافقة لنظام كهروضوئي ذي استطاعة محدودة. حيث تبين أن المردود الطاقي يتراوح بين 23 إلى 67 % حسب طريقة استخدام الهيدروجين المنتج.